Reducing risks and seizing opportunities: integrating biodiversity into food and agriculture investments - Negra, C. (Bioversity International, 2017)
This booklet explains how using the Agrobiodiversity Index, companies and governments can reduce operational and reputational risks and seize opportunities, by estimating and monitoring the agrobiodiversity impact of supply chain investments. The Agrobiodiversity Index can also help investors to screen their portfolios for companies and governments that promote agrobiodiversity, as a proxy for operational and reputational risks related to climate change and unsustainable production.